Microbial Characteristics and Genomic Analysis of an ST11 Carbapenem-Resistant Klebsiella pneumoniae Strain Carrying blaKPC−2 Conjugative Drug-Resistant Plasmid - Zeng, Lingyi; Zhang, Jisheng; Hu, Kewang; Li, Jie; Wang, Jianmin; Yang, Chengru; Huang, Wan; Yin, Lining; Zhang, Xiaoli (Frontiers in Public Health, 2022)
Background: The ST11 (Sequence type 11) CRKP (carbapenem-resistant Klebsiella pneumoniae) carrying blaKPC-2 has been widespread all over the world, and it has been reported frequently in China. The blaKPC-2 located on the mobile genetic element brings tremendous pressure to control the spread and outbreak of resistant bacteria. Whole-genome sequencing (WGS) technology can comprehensively and in-depth display the molecular characteristics of drug-resistant bacteria, providing a basis for evaluating the genetic diversity within the CRKP genome. Methods: The ST11 CRKP in this study was collected in the intensive care unit of a major teaching hospital. PCR (polymerase chain reaction) and Sanger sequencing confirmed the existence of blaKPC-2. AST-GN card and microbroth dilution test were used for antimicrobial susceptibility testing. The transferability of plasmid was verified by conjugation test. The whole genome is sequenced using Illumina HiSeq short-read and Oxford Nanopore long-read sequencing technology. Results: The study strain was named CRKP63, which is a multi-drug resistance bacteria, which carries blaKPC-2 and blaSHV-182. Its genome consists of a circular chromosome of 5,374,207bp and an IncFII plasmid named pKPC-063001of 359,625bp. In the drug-resistant plasmid pKPC-063001, the key carbapenem resistance gene blaKPC-2 was located in the genetic context with insertion sequence ISKpn27 upstream and ISKpn6 downstream and bracketed by IS26. The three copies of the IS26–ISKpn27–blaKPC-2–ISKpn6–IS26 unit were present in tandem. blaKPC-2 can be transferred horizontally between other species by conjugation, the complete T4SS structure helps to improve the adaptability of bacteria to the external environment, strengthen the existence of drug-resistant bacteria and accelerate the spread of drug resistance. Conclusion: High-throughput sequencing has discovered the different surrounding environment of blaKPC-2, which provides a new idea for further revealing the transmission and inheritance of blaKPC-2 at the molecular level. In order to control the further spread and prevalence of drug-resistant bacteria, we should pay close attention to the changes in the genetic environment of blaKPC-2, and further study the transcription and expression of T4SS.